1989
DOI: 10.1159/000153860
|View full text |Cite
|
Sign up to set email alerts
|

Commingling in the Distributions of Immunoglobulin Levels

Abstract: Commingling in the distributions of five immunoglobulins from a Canadian sample of 810 Caucasians and IgE from a US sample of 935 Caucasians was investigated. For both the Canadian and US samples significant commingling was found in the child’s but not the adult’s IgE distribution. Contrary to expectations based upon the major gene hypothesis for IgM, we found no evidence for commingling in the IgM distribution. Finally, the distributions of IgA, IgD and IgG all evidenced significant commingling that may be th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 10 publications
(10 reference statements)
0
7
0
Order By: Relevance
“…‘Unilateral dystonic/tonic posturing’ was considered present only if one upper extremity showed sustained, involuntary or unnatural posturing lasting more than 10 s, including unnatural immobility of one arm relative to the other [3, 8]. If dystonic/tonic posturing was observed at both upper extremities simultaneously or within 5 s, it was not considered as a lateralizing sign.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…‘Unilateral dystonic/tonic posturing’ was considered present only if one upper extremity showed sustained, involuntary or unnatural posturing lasting more than 10 s, including unnatural immobility of one arm relative to the other [3, 8]. If dystonic/tonic posturing was observed at both upper extremities simultaneously or within 5 s, it was not considered as a lateralizing sign.…”
Section: Methodsmentioning
confidence: 99%
“…Individual clinical symptoms during seizure have been investigated for their lateralizing significance [3,4,5,6,7]. However, the incidence and the lateralization accuracy of individual clinical symptoms vary among studies [8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…This method has been described in detail in several sources (MacLean et al 1976;McGue et al 1989;Levy et al 1993). The data available from the 185 haloperidol-treated rats and 127 control rats were subject to mixture analysis on each of the two treatment groups separately.…”
Section: Statistics Mixture Analysismentioning
confidence: 99%
“…Preliminary inspection of the phenotypic distributions suggested that the logarithmic scale is preferred for IgD, lgG, and IgE, the transformation accounting for most of the deviations from normality (McGue et al 1989). Each of the immunoglobulin phenotypes subsequently was transformed prior to analysis in the following manner.…”
Section: Family Studies and Phenotypesmentioning
confidence: 99%
“…The resulting scores were transformed so as to achieve approximate normality and to minimize spurious evidence in favor of major gene effects, according to the following formula: y = r/p[(x/r + I)P-I], where, x is the age-adjusted, standardized score, r is a scale factor chosen such that every (x/r + 1) > 0, and p is the power transformation parameter (MacLean et al 1976). The parameter p for each immunoglobulin was estimated under the conservative assumption of a single distribution with r set to 6 (McGue et al 1989). …”
Section: Family Studies and Phenotypesmentioning
confidence: 99%